La agricultura de precisión como fuente de alimento global para 2050 - Gonzales, Marcella (2018)
The objective of this essay is to provide some thoughts on how technology is changing world agriculture. Big data is improving productivity of crops and reducing pollution. In this technological evolution, while farmers develop new tools to achieve superior output performance, with a scope in cultivated area, precision agriculture is making a personalized analysis per crop, by using, for example, global positioning system (GPS). By affecting farm labor productivity positively and increasing agricultural output considerably, this could make of food shortages something of the past.